Comprovação de claim de ativos cosméticos in vitro utilizando modelo tridimensional de cultura celular em adipócitos - Ueoka, Andreza Rodrigues [UNIFESP] (2020)
In vitro safety and efficacy assesment models of cosmetic actives are increasingly popular as there is a ban on the use of animals in 39 countries and some Brazilian states. In this context, a new in vitro model of three-dimensional coculture of adipose and endothelial cells was proposed for the in vitro safety assessment and proof of efficacy for improvement skin appearence of cellulite and aged skin. The safety trials of the assets Centella asiatica, horse chestnut, witch hazel, caffeine, Blend and Ecoblend were performed by cytotoxicity assays in three different types of cells strains, phototoxicity, genotoxicity with flow cytometry method and cytotoxicity in three-dimensional coculture of adipose and endothelial cells and the efficacy assay was performed by the Oil Red O method in single-layer cells and three-dimensional coculture. The results showed that the active Centella asiatica, Blend and caffeine in the concentration 2.5% were more cytotoxic in endothelial cells than in Balb/c 3T3 cells, since they provided a decreasement of about 10%, 98% and 20%, respectively. In the cytotoxicity assay, the active Centella asiatica, witch hazel, Blend and caffeine at the concentration of 2.5% were more cytotoxic in 3T3-L1 cells than in Balb/c 3T3 cells, since they led to a decreasement of about 8%, 24%, 99% and 20%, respectively. None of the evaluated actives presented phototoxicity and genotoxicity. The three-dimensional coculture of adipose and endothelial cells presented greater cellular viability when compared to single-layer cells at the same concentration. In the efficacy test, the Centella asiatica, horse chestnut, witch hazel, caffeine and Blend in the highest test concentration caused a reduction in the amount of intracellular lipids around 40%, 12%, 27%, 35% and 30%, respectively. It was possible to conclude that the proposed model of three-dimensional co-culture for in vitro evaluation of safety and efficacy of cosmetic assets was effective and advantageous in relation to the 2D model, since it presents better representation of adipose tissue with concentrations closer to cell use and organization more similar to the in vivo system.